Ebola Emergency Preparedness: Simulation Training for Frontline Health Care Professionals - Dara Ann O'Keeffe; Dorothy Bradley; Linda Evans; Nirma Bustamante; Matthew Timmel; Roopa Akkineni; Deborah Mulloy; Eric Goralnick; Charles Pozner (Association of American Medical Colleges, 2016)
Abstract Introduction At Brigham and Women's Hospital, we identified the need for a comprehensive training program designed to prepare frontline staff to safely manage a patient with Ebola viral disease (EVD). The primary goal of this program was to ensure the safety of staff, patients, and the general public by training staff in the correct use of personal protective equipment (PPE) before, during, and after care of patients with EVD. Methods We delivered a 4-hour experiential training program to frontline health care professionals who would be expected to care for a patient with EVD. The program occurred in a simulation center with multiple flexible spaces and consisted of demonstration, multiple skills practice sessions, and a patient simulation case. We analyzed completed pre- and posttraining questionnaires. The questionnaire assessed their subjective level of confidence in three key areas: donning and doffing PPE, performing clinical skills while wearing PPE, and management of a contamination breach. Results This program was effectively deployed in the STRATUS Center for Medical Simulation over a 4-month period, with 220 health care professionals participating in the training and 195 participants completing the pre-/posttraining questionnaires. Our intervention significantly increased the confidence of participants on each primary objective (p = .001 for all three stations). Discussion This interprofessional simulation-based program has been shown to be a well-received method of training clinicians to manage patients collaboratively during an EVD outbreak. Our intent is that the skills taught in this training program would also be transferable to management of other infectious diseases in the clinical setting.